The art and science of serious game design: a quasi-experimental study based on self-determination theory in traditional Chinese culture education - Yang, Jiqiang; Li, Ran (Frontiers in Psychology, 2025)
IntroductionDrawing upon self-determination theory, this research investigates methods to enhance motivation in educational settings through the use of serious games by addressing the fundamental psychological needs for autonomy, competence, and relatedness.MethodsThree strategies were proposed to meet these needs: diversifying learning resource presentations, creating appropriate challenges, and integrating relationships into the narrative framework. A serious game incorporating traditional Chinese culture was developed and compared to a short documentary film for learning efficacy. The study involved 60 college students from two natural classes who participated in either a 15-minute gameplay session or a 15-minute video-watching session, followed by a 10-minute discussion. Post-test scores and learning motivation were assessed to evaluate the effectiveness of both methods.ResultsNo significant difference in post-test scores was observed between the two groups, indicating that the serious game was as effective as the traditional documentary in enhancing academic performance. However, the serious game significantly outperformed the documentary in enhancing learning motivation, despite being perceived as less authentic. The immersive and interactive elements of the game were found to boost engagement and interest among students.DiscussionThe results underscore the potential of serious games to create engaging and motivating educational environments that cater to diverse student populations while maintaining academic rigor. The findings suggest that serious games can be a valuable tool in education, particularly for enhancing motivation and engagement, even when traditional methods are equally effective in terms of academic performance.